The effect on rainfall on 11.2 GHz microwave link performance / Daud Jonit and Mustapa Kamal Mohd. Kassim - Jonit, Daud; Mohd. Kassim, Mustapa Kamal (1994)
Nowadays the development of digital radio are growing very attenuation at the rapidly. A knowledge relay systems of the rain frequency of operation is desirable in designing a reliable communication system at a particular location. The wave propagation at can suffer from rain effects scattering and depolarization. frequencies of 10 GHz such as attenuati9n, The magnitude of these effects depends on rain characteristics. to find the rain effects performance at 11.2 GHz. on the Our objective was microwave link Continuous recording of signal level and rainfall has been carried out for four months. This paper presents results of the propagation experiments undertaken for the link between Bukit Gasing base station and Kelana Jaya base station. The microwave attenuation was recorded using Yokogawa chart recorder at the AGC point of the receiver of DRS 140/11200 SEL microwave equipment. The rain measurement had been done at meteorological department located near Bukit Gasing. The line-of-sight distance between the two radio base stations is 6.51 Km.